A modified hemp core powder composite polyurethane foam material and preparation method thereof
By wrapping titanium oxygen material on the hemp core powder and forming a silicon oxygen composite antibacterial system, the problem of rapid decline in antibacterial performance of hemp modified polyurethane foamed materials is solved, and the durability and stability of antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411864020.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The antibacterial properties of hemp-modified polyurethane foamed materials rapidly decline after the use time is extended, resulting in its loss of antibacterial effect.
Titanium oxygen material is used to wrap the hemp core powder, and form a composite antibacterial system through silicon oxygen polycondensation to prevent the loss of antibacterial substances. At the same time, the restorability of titanium oxygen material is used to enhance antibacterial properties.
It effectively solves the problem of the antibacterial performance of hemp-modified polyurethane foaming materials, extends the duration of the antibacterial effect, and improves the stability of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane foam materials, and specifically relates to a modified hemp core powder composite polyurethane foam material and a preparation method thereof. Background Art
[0002] Polyurethane is a polymer formed by the gradual addition polymerization of polyether, polyester polyol and polyisocyanate containing hydroxyl groups. The polymer is widely used in foam plastics, coatings, elastomers and elastic fibers due to its excellent performance. Among them, polyurethane foam accounts for 70% of the total amount of polyurethane and is the main product of polyurethane materials. In use, polyurethane foam materials do not have antibacterial properties and are very easy to form bacterial growth. In response to this problem, hemp-modified polyurethane foam materials came into being. The hemp-modified polyurethane foam materials not only have good antibacterial effects, but also show excellent hardness and strength, which improves the practicality of hemp-modified polyurethane foam materials. However, although hemp has good antibacterial and antibacterial properties in the early stage, this property comes from the unique antibacterial substances such as alkaloids and phenols contained in hemp. However, as the use time increases, the antibacterial performance decreases sharply with the loss of antibacterial substances until the antibacterial performance is lost. Summary of the invention
[0003] In view of the problems in the prior art, the present invention provides a modified hemp core powder composite polyurethane foam material, which solves the problem of antibacterial durability of hemp modified polyurethane foam. By utilizing the encapsulation, antibacterial and antibacterial properties and recoverability of titanium oxide materials, an organic-inorganic composite antibacterial and antibacterial system can be formed with the antibacterial material in the hemp core, and the antibacterial material is wrapped by silicon oxide materials, which effectively solves the problem of loss of the antibacterial material.
[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:
[0005] A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0006] 30-50 parts of polymer polyol, 10-40 parts of modified hemp core powder, 20-30 parts of flame retardant, 1-2 parts of catalyst, 3-4 parts of foaming agent, 1-2 parts of foam stabilizer, 65-80 parts of organic polyisocyanate, and 0.5-1 part of white oil.
[0007] The polymer polyol is LPOP-36 / 30 or LPOP-36 / 28G.
[0008] The modified hemp core powder adopts titanium oxide modified hemp core powder. The hemp core is an absorbent core made of a pure natural plant fiber extracted from hemp stalks. It has many cavities and pores inside and contains unique antibacterial substances such as alkaloids and phenols. As the use time increases and the number of cleanings increases, the antibacterial substances in the hemp core are seriously lost, which will cause its antibacterial performance to drop rapidly. Titanium oxide material is a titanium dioxide-based material, which is an inorganic antibacterial material and can achieve a wide-area antibacterial effect. Wrapping the titanium oxide material on the surface of the hemp core powder can utilize the surface pore structure formed by silicon oxide polycondensation to reduce the release of antibacterial substances and increase the life of the organic-inorganic composite antibacterial system. The antibacterial performance of the titanium oxide material itself can be restored, and the antibacterial property can be restored only by light exposure. The preparation method of the titanium oxide modified hemp core powder comprises the following steps: a1, grinding the hemp core at a constant temperature, and obtaining the hemp core powder after sieving, wherein the constant temperature grinding temperature is 5-30°C, and the grinding pressure is 0.3-0.5MPa; this step utilizes a constant pressure extrusion method to granulate the hemp core, and controls the friction heat problem of grinding by constant temperature, thereby obtaining a refined material with a structure similar to that of the substance, and finally separates the ground impurities by sieving, and the sieving utilizes pores to obtain hemp core powder with a relatively clean particle size, and at the same time, removes the debris generated by grinding by physical separation, ensuring that the particle size of the hemp core powder is relatively similar; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, and then quickly stirring the hemp core powder. Stir, take out and let it stand for 1-3h to obtain coated hemp core powder, the mass ratio of tetraethyl titanate to ether is 1:3-5, the stirring speed is 100-300r / min, the mass of hemp core powder to ether is 1:10-15, the rapid stirring speed is 1000-3000r / min, the time is 5-10s, and the standing temperature is 30-35°C; this step utilizes the miscibility of tetraethyl titanate in ether to form a homogeneous ether solution of tetraethyl titanate; then add the hemp core powder and stir rapidly, because the pores and holes of the hemp core powder contain a large number of bubbles, which cannot be quickly discharged in a short period of rapid stirring. Therefore, when the hemp core powder is taken out, the internal bubbles are not discharged, and tetraethyl titanate is formed on the surface. Ethyl ester-ether liquid film, at the standing temperature, ether gradually evaporates, thereby forming tetraethyl titanate coated hemp core powder, and at the same time, during the standing process, the liquid fluidity of tetraethyl titanate itself can fill the gaps after the ether evaporates, thereby forming a homogeneous tetraethyl titanate liquid film; a3, the coated hemp core powder is allowed to stand for 20-30 minutes to obtain titanate-wrapped hemp core powder, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the temperature is 30-50°C; this step utilizes the hydrolysis characteristics of tetraethyl titanate, cooperates with the water vapor in the atmosphere and the hygroscopicity of the hemp core powder, improves the hydrolysis rate of tetraethyl titanate, and forms in-situ hydrolysis of tetraethyl titanate, thereby obtaining titanate-modified hemp core powder;a4, add 3-aminopropyl triethoxysilane and ethyl cellulose to ether and stir evenly, then add titanic acid coated hemp core powder and stir at low temperature for 2-4 minutes, take out and dry to obtain secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 10-14:1, and the mass ratio of 3-aminopropyl triethoxysilane to ether is 1:13-15, the stirring speed for uniform stirring is 100-400r / min, the mass ratio of titanic acid coated hemp core powder to ether is 1:18-20, The low-temperature stirring temperature is 5-10°C, the stirring speed is 100-200r / min, and the drying temperature is 40-50°C; this step utilizes the solubility of 3-aminopropyltriethoxysilane and ethyl cellulose in ether to form a homogeneous dispersion effect. During the low-temperature and low-speed stirring process, titanic acid wraps the surface of the hemp core powder to form a liquid film, and the ether is removed during drying to form a composite film of ethyl cellulose and 3-aminopropyltriethoxysilane; a5, the secondary coated hemp core powder is left to stand for 20-30 minutes, sealed sintered and ethanol immersed The titanium oxide modified hemp core powder is soaked and dried after being taken out, the static atmosphere is a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor is 1:8-10, the static temperature is 60-70°C, the sealed sintering adopts double gradient heating, the first gradient heating temperature is 100-120°C, the time is 0.5-1h, the second gradient heating temperature is 180-200°C, the time is 1-2h, the atmosphere is a nitrogen atmosphere, and the solid-liquid mass ratio in the soaking treatment is 1:5-7; this step uses an atmosphere containing water vapor to The 3-aminopropyltriethoxysilane in the coated hemp core powder is hydrolyzed in situ to obtain 3-aminopropyltrihydroxysilane, and in the subsequent first gradient heating, ethyl cellulose maintains good attachment stability, and the silanol group is condensed in situ to form a silicon-oxygen structure. Therefore, in the first gradient heating, the surface coating will form a silicon-oxygen composite porous film with ethyl cellulose as the spacer material. The composite porous film is rich in silanol and amino groups. With the second gradient heating reaction, the titanium hydroxyl group on the titanic acid and the silanol group form a condensation reaction of the hydroxyl system to achieve good connectivity. The titanium oxide modified hemp core powder prepared by this process has the hemp core powder as the core, and is wrapped with titanium oxide film and silicon oxide film from the inside to the outside, and the titanium oxide film and the silicon oxide film form a condensation connection. The titanium oxide film contains a mesoporous structure, has good fluidity, and forms an organic-inorganic composite structure with the antibacterial substance in the inner core cavity. The silicon oxide film contains mesopores and micropores to form a composite pore structure, maintaining good gas fluidity. Furthermore, the titanium oxide modified hemp core powder is porous inside and is completely wrapped by the titanium oxide film, thereby achieving lightweight under the pore structure system. ;
[0009] The flame retardant is a porous silicon material, and the porous silicon material is rich in silanol. The inorganic flame retardant material itself has a good and stable flame retardant effect, but the certain inertia on the surface of the inorganic flame retardant will lead to its poor stability in the polyurethane foam material, which will cause problems such as the falling off of the inorganic material. To solve this problem, the flame retardant is a porous silicon material. The silicon material has a porous structure and a large number of pore structures, forming a good physical penetration and clamping effect. At the same time, the porous silicon material is rich in silanol, which can form a chemical connection in the polyurethane prepolymerization reaction, thereby improving the connection stability of the silicon material in the polyurethane foam material. The preparation method of porous silicon-oxygen material comprises the following steps: b1, adding 3-chloropropyltrichlorosilane and isobutyltriethoxysilane to ether and stirring evenly to obtain a composite solution, wherein the mass ratio of the 3-chloropropyltrichlorosilane to the isobutyltriethoxysilane is 3:1-2, the concentration of the 3-chloropropyltrichlorosilane in the ether is 300-500g / L, the stirring speed of the stirring evenly is 400-600r / min, and the temperature is 5-10°C; in this step, 3-chloropropyltrichlorosilane and isobutyltriethoxysilane in ether are added to the ether and stirred evenly to obtain a composite solution. b2, adding ethyl cellulose to the composite solution, performing low-temperature ultrasonic treatment for 20-30 minutes, and then standing for 2-3 hours to obtain a viscous solution, wherein the concentration of the ethyl cellulose in the composite solution is 500-800 g / L, the temperature of the low-temperature ultrasonic treatment is 5-10°C, the ultrasonic frequency is 60-80kHz, the temperature of the standing treatment is 30-35°C, and the pressure is 90-95% of the atmospheric pressure. This step utilizes the good solubility of ethyl cellulose in ether. The solvent has good solubility and can be quickly dispersed in the mixed solution to achieve a fully mixed effect. The high-frequency vibration of low-temperature ultrasound improves the full mixing and homogenization dispersion of 3-chloropropyltrichlorosilane, isobutyltriethoxysilane and ethyl cellulose in ether. During the static treatment, ether has good volatility, which effectively controls the removal of the solvent and effectively controls the overall viscosity. b3, spraying the viscous liquid into the reactor to obtain deposited particles by deposition. The spraying speed is 3-5mL / min and the spraying area is 200-400cm 2, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, and the deposition temperature is 40-45°C; in this step, the viscous liquid is sprayed into the reactor by spraying, and the ether is rapidly evaporated under the temperature system. At this time, the viscous liquid is sprayed to form solid particles, which are composed of ethyl cellulose, 3-chloropropyltrichlorosilane and isobutyltriethoxysilane. The atmosphere in the reactor contains water vapor, which can form a hydrolysis reaction with 3-chloropropyltrichlorosilane and isobutyltriethoxysilane, that is, the deposited particles are solid particles composed of 2-hydroxypropyltrihydroxysilane, isobutyltrihydroxysilane and ethyl cellulose; b4, the deposited particles are kept at a constant temperature for 2-4 hours, then placed in ethanol for ultrasonic treatment for 20-30 minutes, and filtered The porous silicon-oxygen material is obtained by post-drying, the constant temperature standing temperature is 110-120°C, the atmosphere is a nitrogen atmosphere, the solid-liquid mass ratio of the ultrasonic treatment is 1:5-7, the temperature is 20-30°C, the ultrasonic frequency is 60-90kHz, and the drying temperature is 80-90°C; this step promotes the polycondensation reaction of the hydrolyzate of 3-chloropropyltrichlorosilane and isobutyltriethoxysilane by constant temperature standing, ethyl cellulose maintains its own stability and inertness, ensures that the polycondensation reaction is an in-situ reaction, ethanol solubility in ethyl cellulose and insolubility in silicon-oxygen polycondensate, can quickly strip ethyl cellulose into ethanol under ultrasonic environment, thereby obtaining a modified silicon-oxygen material, at this time the silicon-oxygen material is formed by silanol polycondensation, not only contains a large amount of surface area, but also the surface area can contain silicon hydroxyl activity.
[0010] The catalyst is triethylenediamine.
[0011] The foaming agent is water.
[0012] The foam stabilizer is silicone oil AK8805.
[0013] The organic polyisocyanate is toluene diisocyanate.
[0014] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0015] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 300-500 r / min and the stirring temperature is room temperature;
[0016] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1000-2000 r / min and the time is 20-40 s;
[0017] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2000-3000r / min, the time is 7-10s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 20-24h.
[0018] It can be seen from the above description that the present invention has the following advantages:
[0019] 1. The present invention solves the problem of the antibacterial durability of hemp-modified polyurethane foam. By utilizing the encapsulation, antibacterial and antifungal properties and recoverability of titanium oxide materials, an organic-inorganic composite antibacterial and antifungal system can be formed with the antibacterial material in the hemp core. The antibacterial material is encapsulated by silicon oxide materials, which effectively solves the problem of the loss of the antibacterial material.
[0020] 2. The present invention forms a silicon oxide layer on the surface of the titanium oxide film, ensuring stable connectivity between the silicon oxide layer and the titanium oxide film. At the same time, the silicon oxide layer wraps the titanium oxide film, effectively solving the corrosion problem of the titanium oxide material after excitation and activation.
[0021] 3. The present invention promotes the polyurethane prepolymerization reaction with a multi-hydroxy structure by utilizing the characteristic that the silicon oxide layer wrapped on the surface of the titanium oxide film is rich in silicon hydroxyl groups. DETAILED DESCRIPTION
[0022] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.
[0023] Example 1 A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0024] 30 parts of polymer polyol, 10 parts of modified hemp core powder, 20 parts of flame retardant, 1-2 parts of catalyst, 3 parts of foaming agent, 1 part of foam stabilizer, 65 parts of organic polyisocyanate, and 0.5 parts of white oil.
[0025] The polymer polyol used is LPOP-36 / 30 produced by Shandong Longhua New Materials Co., Ltd.
[0026] The modified hemp core powder adopts titanium oxide modified hemp core powder, and the preparation method of the titanium oxide modified hemp core powder comprises the following steps: a1, grinding the hemp core at constant temperature, and obtaining the hemp core powder after sieving, wherein the temperature of the constant temperature grinding is 5° C., and the grinding pressure is 0.3 MPa; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, and then quickly stirring the hemp core powder, taking it out and standing it for 1 hour to obtain the coated hemp core powder, wherein the mass ratio of tetraethyl titanate to ether is 1:3, and the stirring speed is 1:3. 00r / min, the mass of the hemp core powder and the ether is 1:10, the speed of rapid stirring is 1000r / min, the time is 5-10s, and the static temperature is 30°C; a3, the coated hemp core powder is allowed to stand for 20min to obtain the titanate-coated hemp core powder, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 30°C; a4, 3-aminopropyl triethoxysilane and ethyl cellulose are added to the ether and stirred evenly, and then added The titanium acid coated hemp core powder is stirred at low temperature for 2 minutes, taken out and dried to obtain the secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 10:1, and the mass ratio of 3-aminopropyl triethoxysilane to diethyl ether is 1:13, the stirring speed is 100r / min, the mass ratio of the titanium acid coated hemp core powder to diethyl ether is 1:18, the low temperature stirring temperature is 5°C, the stirring speed is 100r / min, and the drying temperature is 40°C; a5, The secondary coated hemp core powder is left to stand for 20 minutes, sealed and sintered, and immersed in ethanol, and then taken out and dried to obtain titania-modified hemp core powder. The standing atmosphere is a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor is 1:8. The standing temperature is 60°C. The sealed sintering adopts double gradient heating. The first gradient heating temperature is 100°C for 0.5h, and the second gradient heating temperature is 180°C for 1h. The atmosphere is a nitrogen atmosphere, and the solid-liquid mass ratio in the immersion treatment is 1:5.
[0027] The flame retardant adopts a porous silicon material, and the porous silicon material is rich in silanol groups; the preparation method of the porous silicon material comprises the following steps: b1, adding 3-chloropropyltrichlorosilane and isobutyltriethoxysilane to ether and stirring evenly to obtain a composite solution, the mass ratio of the 3-chloropropyltrichlorosilane to the isobutyltriethoxysilane is 3:1, the concentration of the 3-chloropropyltrichlorosilane in the ether is 300g / L, the stirring speed of the stirring evenly is 400r / min, the temperature is 400r / min, and the stirring speed is 400r / min. b2, adding ethyl cellulose to the composite solution and performing low-temperature ultrasound for 20 minutes, and then standing for 2 hours to obtain a viscous solution, wherein the concentration of ethyl cellulose in the composite solution is 500 g / L, the temperature of the low-temperature ultrasound is 5°C, the ultrasonic frequency is 60 kHz, the temperature of the standing treatment is 30°C, and the pressure is 90% of the atmospheric pressure; b3, spraying the viscous solution into a reactor to obtain deposited particles by deposition, wherein the spraying speed is 3-5 mL / min, and the spraying area is 200 cm 2 , the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the deposition temperature is 40°C; b4, the deposited particles are kept at a constant temperature for 2 hours, and then placed in ethanol for ultrasonic treatment for 20 minutes, filtered and dried to obtain a porous silicon oxide material, the constant temperature standing temperature is 110°C, the atmosphere is a nitrogen atmosphere, the solid-liquid mass ratio of the ultrasonic treatment is 1:5, the temperature is 20°C, the ultrasonic frequency is 60kHz, and the drying temperature is 80°C.
[0028] The catalyst is triethylenediamine.
[0029] The foaming agent is water.
[0030] The foam stabilizer is silicone oil AK8805.
[0031] The organic polyisocyanate is toluene diisocyanate.
[0032] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0033] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 300 r / min and the stirring temperature is room temperature;
[0034] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1000 r / min and the time is 20 s;
[0035] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2000r / min, the time is 7s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 20h.
[0036] Example 2 A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0037] 50 parts of polymer polyol, 40 parts of modified hemp core powder, 30 parts of flame retardant, 2 parts of catalyst, 4 parts of foaming agent, 2 parts of foam stabilizer, 80 parts of organic polyisocyanate, and 1 part of white oil.
[0038] The polymer polyol adopts LPOP-36 / 28G.
[0039] The modified hemp core powder adopts titanium oxide modified hemp core powder, and the preparation method of the titanium oxide modified hemp core powder comprises the following steps: a1, grinding the hemp core at constant temperature, and obtaining the hemp core powder after sieving, wherein the temperature of the constant temperature grinding is 30° C., and the grinding pressure is 0.5 MPa; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, and then quickly stirring the hemp core powder, taking it out and letting it stand for 3 hours to obtain the coated hemp core powder, wherein the mass ratio of tetraethyl titanate to ether is 1:5, and the stirring speed is 300r / min, the mass of the hemp core powder and the ether is 1:15, the speed of rapid stirring is 3000r / min, the time is 10s, and the static temperature is 35°C; a3, the coated hemp core powder is allowed to stand for 30min to obtain the titanate-coated hemp core powder, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the temperature is 50°C; a4, 3-aminopropyl triethoxysilane and ethyl cellulose are added to the ether and stirred evenly, and then added The titanium acid coated hemp core powder is stirred at low temperature for 4 minutes, taken out and dried to obtain the secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 14:1, and the mass ratio of 3-aminopropyl triethoxysilane to diethyl ether is 1:15, the stirring speed is 400r / min, the mass ratio of the titanium acid coated hemp core powder to diethyl ether is 1:20, the low temperature stirring temperature is 10°C, the stirring speed is 200r / min, and the drying temperature is 50°C; a5, The secondary coated hemp core powder is left to stand for 30 minutes, sealed and sintered, and soaked in ethanol, then taken out and dried to obtain titania-modified hemp core powder. The standing atmosphere is a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor is 1:10. The standing temperature is 70°C. The sealed sintering adopts double gradient heating. The first gradient heating temperature is 120°C for 1 hour, and the second gradient heating temperature is 200°C for 2 hours. The atmosphere is a nitrogen atmosphere. The solid-liquid mass ratio in the soaking treatment is 1:7.
[0040] The flame retardant adopts a porous silicon material, and the porous silicon material is rich in silanol groups; the preparation method of the porous silicon material comprises the following steps: b1, adding 3-chloropropyltrichlorosilane and isobutyltriethoxysilane to ether and stirring evenly to obtain a composite solution, the mass ratio of the 3-chloropropyltrichlorosilane to the isobutyltriethoxysilane is 3:2, the concentration of the 3-chloropropyltrichlorosilane in the ether is 500g / L, the stirring speed of the stirring evenly is 600r / min, the temperature is 400℃, and the stirring speed is 1000rpm. b2, adding ethyl cellulose to the composite solution and performing low-temperature ultrasound for 30 minutes, and then standing for 3 hours to obtain a viscous solution, wherein the concentration of ethyl cellulose in the composite solution is 800 g / L, the temperature of the low-temperature ultrasound is 10°C, the ultrasonic frequency is 80 kHz, the temperature of the standing treatment is 35°C, and the pressure is 95% of the atmospheric pressure; b3, spraying the viscous solution into a reactor, and obtaining deposited particles by deposition, wherein the spraying speed is 5 mL / min, and the spraying area is 400 cm 2 , the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 12:1, and the deposition temperature is 45°C; b4, the deposited particles are kept at a constant temperature for 4 hours, and then placed in ethanol for ultrasonic treatment for 30 minutes, filtered and dried to obtain a porous silicon oxide material, the constant temperature standing temperature is 120°C, the atmosphere is a nitrogen atmosphere, the solid-liquid mass ratio of the ultrasonic treatment is 1:7, the temperature is 30°C, the ultrasonic frequency is 90kHz, and the drying temperature is 90°C.
[0041] The catalyst is triethylenediamine.
[0042] The foaming agent is water.
[0043] The foam stabilizer is silicone oil AK8805.
[0044] The organic polyisocyanate is toluene diisocyanate.
[0045] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0046] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 500 r / min and the stirring temperature is room temperature;
[0047] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 2000 r / min and the time is 40 s;
[0048] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 3000r / min, the time is 10s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 24h.
[0049] Example 3 A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0050] 40 parts of polymer polyol, 30 parts of modified hemp core powder, 25 parts of flame retardant, 2 parts of catalyst, 3 parts of foaming agent, 2 parts of foam stabilizer, 75 parts of organic polyisocyanate, and 0.8 parts of white oil.
[0051] The polymer polyol adopts LPOP-36 / 30.
[0052] The modified hemp core powder adopts titanium oxide modified hemp core powder, and the preparation method of the titanium oxide modified hemp core powder comprises the following steps: a1, grinding the hemp core at constant temperature, and obtaining the hemp core powder after sieving, wherein the temperature of the constant temperature grinding is 20°C, and the grinding pressure is 0.4MPa; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, and then quickly stirring the hemp core powder, taking it out and standing it for 2 hours to obtain the coated hemp core powder, wherein the mass ratio of tetraethyl titanate to ether is 1:4, and the stirring speed is uniform. The stirring speed is 200r / min, the mass ratio of the hemp core powder to the ether is 1:13, the rapid stirring speed is 2000r / min, the time is 8s, and the static temperature is 33°C; a3, the coated hemp core powder is allowed to stand for 25min to obtain the titanate-coated hemp core powder, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, and the temperature is 40°C; a4, 3-aminopropyl triethoxysilane and ethyl cellulose are added to the ether and stirred evenly, and then added The titanium acid coated hemp core powder is stirred at low temperature for 3 minutes, taken out and dried to obtain the secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 12:1, and the mass ratio of 3-aminopropyl triethoxysilane to diethyl ether is 1:14, the stirring speed is 300r / min, the mass ratio of the titanium acid coated hemp core powder to diethyl ether is 1:19, the low temperature stirring temperature is 8°C, the stirring speed is 150r / min, and the drying temperature is 45°C; a5, The secondary coated hemp core powder was left to stand for 25 minutes, sealed and sintered, and soaked in ethanol, then taken out and dried to obtain titania-modified hemp core powder. The standing atmosphere was a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor was 1:9. The standing temperature was 65°C. The sealed sintering adopted double gradient heating. The first gradient heating temperature was 110°C for 1 hour, and the second gradient heating temperature was 190°C for 2 hours. The atmosphere was a nitrogen atmosphere. The solid-liquid mass ratio in the soaking treatment was 1:6.
[0053] The flame retardant adopts a porous silicon material, and the porous silicon material is rich in silanol groups; the preparation method of the porous silicon material comprises the following steps: b1, adding 3-chloropropyltrichlorosilane and isobutyltriethoxysilane to ether and stirring evenly to obtain a composite solution, the mass ratio of the 3-chloropropyltrichlorosilane to the isobutyltriethoxysilane is 3:1, the concentration of the 3-chloropropyltrichlorosilane in the ether is 400g / L, the stirring speed of the stirring evenly is 500r / min, the temperature is 400℃, and the stirring speed is 500r / min. b2, adding ethyl cellulose to the composite solution and performing low-temperature ultrasound for 25 minutes, and then standing for 3 hours to obtain a viscous solution, wherein the concentration of ethyl cellulose in the composite solution is 700 g / L, the temperature of the low-temperature ultrasound is 8°C, the ultrasonic frequency is 70 kHz, the temperature of the standing treatment is 33°C, and the pressure is 93% of the atmospheric pressure; b3, spraying the viscous solution into a reactor to obtain deposited particles by deposition, wherein the spraying speed is 4 mL / min, and the spraying area is 300 cm 2 , the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 11:1, and the deposition temperature is 43°C; b4, the deposited particles are kept at a constant temperature for 3 hours, and then placed in ethanol for ultrasonic treatment for 25 minutes, filtered and dried to obtain a porous silicon oxide material, the constant temperature standing temperature is 115°C, the atmosphere is a nitrogen atmosphere, the solid-liquid mass ratio of the ultrasonic treatment is 1:6, the temperature is 25°C, the ultrasonic frequency is 80kHz, and the drying temperature is 85°C.
[0054] The catalyst is triethylenediamine.
[0055] The foaming agent is water.
[0056] The foam stabilizer is silicone oil AK8805.
[0057] The organic polyisocyanate is toluene diisocyanate.
[0058] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0059] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 400 r / min and the stirring temperature is room temperature;
[0060] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1500 r / min and the time is 30 s;
[0061] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2500r / min, the time is 9s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 22h.
[0062] Example 4 A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0063] 40 parts of polymer polyol, 30 parts of modified hemp core powder, 25 parts of flame retardant, 2 parts of catalyst, 3 parts of foaming agent, 2 parts of foam stabilizer, 75 parts of organic polyisocyanate, and 0.8 parts of white oil.
[0064] The polymer polyol adopts LPOP-36 / 30.
[0065] The modified hemp core powder adopts titanium oxide modified hemp core powder, and the preparation method of the titanium oxide modified hemp core powder comprises the following steps: a1, grinding the hemp core at constant temperature, and obtaining the hemp core powder after sieving, wherein the temperature of the constant temperature grinding is 20°C, and the grinding pressure is 0.4MPa; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, and then quickly stirring the hemp core powder, taking it out and standing it for 2 hours to obtain the coated hemp core powder, wherein the mass ratio of tetraethyl titanate to ether is 1:4, and the stirring speed is uniform. The stirring speed is 200r / min, the mass ratio of the hemp core powder to the ether is 1:13, the rapid stirring speed is 2000r / min, the time is 8s, and the static temperature is 33°C; a3, the coated hemp core powder is allowed to stand for 25min to obtain the titanate-coated hemp core powder, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, and the temperature is 40°C; a4, 3-aminopropyl triethoxysilane and ethyl cellulose are added to the ether and stirred evenly, and then added The titanium acid coated hemp core powder is stirred at low temperature for 3 minutes, taken out and dried to obtain the secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 12:1, and the mass ratio of 3-aminopropyl triethoxysilane to diethyl ether is 1:14, the stirring speed is 300r / min, the mass ratio of the titanium acid coated hemp core powder to diethyl ether is 1:19, the low temperature stirring temperature is 8°C, the stirring speed is 150r / min, and the drying temperature is 45°C; a5, The secondary coated hemp core powder was left to stand for 25 minutes, sealed and sintered, and soaked in ethanol, then taken out and dried to obtain titania-modified hemp core powder. The standing atmosphere was a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor was 1:9. The standing temperature was 65°C. The sealed sintering adopted double gradient heating. The first gradient heating temperature was 110°C for 1 hour, and the second gradient heating temperature was 190°C for 2 hours. The atmosphere was a nitrogen atmosphere. The solid-liquid mass ratio in the soaking treatment was 1:6.
[0066] The flame retardant is nano silicon dioxide with a particle size of 300-500nm.
[0067] The catalyst is triethylenediamine.
[0068] The foaming agent is water.
[0069] The foam stabilizer is silicone oil AK8805.
[0070] The organic polyisocyanate is toluene diisocyanate.
[0071] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0072] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 400 r / min and the stirring temperature is room temperature;
[0073] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1500 r / min and the time is 30 s;
[0074] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2500r / min, the time is 9s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 22h.
[0075] Comparative Example 1
[0076] A mass ratio of a modified hemp core powder composite polyurethane foam material:
[0077] 40 parts of polymer polyol, 30 parts of hemp core powder, 25 parts of flame retardant, 2 parts of catalyst, 3 parts of foaming agent, 2 parts of foam stabilizer, 75 parts of organic polyisocyanate, and 0.8 parts of white oil.
[0078] The polymer polyol adopts LPOP-36 / 30.
[0079] The flame retardant is multi-nano silicon dioxide with a particle size of 300-500nm.
[0080] The catalyst is triethylenediamine.
[0081] The foaming agent is water.
[0082] The foam stabilizer is silicone oil AK8805.
[0083] The organic polyisocyanate is toluene diisocyanate.
[0084] The preparation method of the modified hemp core powder composite polyurethane foam material comprises the following steps:
[0085] Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 400 r / min and the stirring temperature is room temperature;
[0086] Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1500 r / min and the time is 30 s;
[0087] Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2500r / min, the time is 9s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 22h.
[0088] Comparative Example 2
[0089] Comparative Example 2 selected commercially available polyurethane foam material.
[0090] Performance Testing
[0091] The products of Examples 1-4 and Comparative Examples 1-2 were used as test samples to perform performance tests, and the results are as follows:
[0092] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A modified hemp core powder composite polyurethane foam material, characterized in that: The mass ratio of the materials is as follows: 30-50 parts of polymer polyol, 10-40 parts of modified hemp core powder, 20-30 parts of flame retardant, 1-2 parts of catalyst, 3-4 parts of foaming agent, 1-2 parts of foam stabilizer, 65-80 parts of organic polyisocyanate, 0.5-1 parts of white oil; The modified hemp core powder adopts titanium oxide modified hemp core powder; The titanium oxide modified hemp core powder is prepared by a method comprising the following steps: a1, grinding the hemp core at a constant temperature, and obtaining hemp core powder after sieving, wherein the constant temperature grinding temperature is 5-30° C. and the grinding pressure is 0.3-0.5 MPa; a2, dissolving tetraethyl titanate in ether and stirring evenly to obtain a homogeneous liquid, then quickly stirring the hemp core powder, taking it out and letting it stand for 1-3 hours to obtain the coated hemp core powder, the mass ratio of tetraethyl titanate to ether is 1:3-5, the stirring speed is 100-300r / min, the mass ratio of the hemp core powder to ether is 1:10-15, the rapid stirring speed is 1000-3000r / min, the time is 5-10s, and the standing temperature is 30-35°C; a3, leaving the coated hemp core powder to stand for 20-30 minutes to obtain titanate-coated hemp core powder, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the temperature is 30-50°C; a4, add 3-aminopropyl triethoxysilane and ethyl cellulose to ether and stir evenly, then add titanic acid-coated hemp core powder and stir at low temperature for 2-4 minutes, take out and dry to obtain secondary coated hemp core powder, the mass ratio of 3-aminopropyl triethoxysilane to ethyl cellulose is 10-14:1, and the mass ratio of 3-aminopropyl triethoxysilane to ether is 1:13-15, the stirring speed for uniform stirring is 100-400r / min, the mass ratio of titanic acid-coated hemp core powder to ether is 1:18-20, the low temperature stirring temperature is 5-10°C, the stirring speed is 100-200r / min, and the drying temperature is 40-50°C; a5. Let the secondary coated hemp core powder stand for 20-30 minutes, perform sealing sintering and ethanol soaking treatment, take it out and dry it to obtain titania-modified hemp core powder. The standing atmosphere is a nitrogen and water vapor atmosphere, and the volume ratio of nitrogen to water vapor is 1:8-10. The standing temperature is 60-70°C. The sealing sintering adopts double gradient heating. The first gradient heating temperature is 100-120°C, the time is 0.5-1h, the second gradient heating temperature is 180-200°C, the time is 1-2h, the atmosphere is a nitrogen atmosphere, and the solid-liquid mass ratio in the soaking treatment is 1:5-7.
2. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The polymer polyol is LPOP-36 / 30 or LPOP-36 / 28G.
3. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The flame retardant is a porous silicon-oxygen material, and the porous silicon-oxygen material is rich in silanol groups.
4. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The catalyst is triethylenediamine.
5. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The foaming agent is water.
6. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The foam stabilizer is silicone oil AK8805.
7. The modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The organic polyisocyanate is toluene diisocyanate.
8. The method for preparing the modified hemp core powder composite polyurethane foam material according to claim 1, characterized in that: The steps include: Step 1, stirring and mixing the polymer polyol, modified hemp core powder and flame retardant to form a mixture, wherein the stirring speed of the stirring and mixing is 300-500 r / min and the stirring temperature is room temperature; Step 2, adding the catalyst, white oil, foaming agent and foam stabilizer into the mixture, and rapidly stirring to obtain a prepolymerized mixture, wherein the rapid stirring speed is 1000-2000 r / min and the time is 20-40 s; Step 3, adding organic polyisocyanate to the prepolymer mixture and stirring at high speed, and then foaming and aging to obtain a modified hemp core powder composite polyurethane foam material, the high-speed stirring speed is 2000-3000r / min, the time is 7-10s, the foaming adopts static free foaming, the aging temperature is room temperature, and the time is 20-24h.
Citation Information
Patent Citations
Hemp stalk core powder modified antibacterial type soft polyurethane composite foaming material
CN105669935A
Quick-drying and flame-retardant multifunctional polyurethane foaming material and preparation method thereof
CN108178914A